Intrinsic photoelectrocatalytic activity in oriented, photonic TiO2 nanotubes. (December 2018) - Fleischer, Christian; Chatzitakis, Athanasios; Norby, Truls
Abstract: In this work, we grow oriented photonic TiO2 nanotubes (TNTs) with a well-established anodization method and their intrinsic catalytic and electronic properties are studied by means of (photo)electrochemical methods. The oriented photonic TNTs are assessed by the R ct C dl (ΩF) product, which is a measure of the intrinsic photoelectrocatalytic activity (IPA) of the material. The R ct C dl product decouples any surface area effects and it can be applied at any potential and accompanied reaction without knowing the actual electrochemically active surface area (EASA). Moreover, electrochemical impedance spectroscopy (EIS) is used in order to investigate the frequency dispersion in the single frequency Mott-Schottky (MS) measurement. The choice of frequency and the frequency dispersion in MS measurements in nanostructured and of high surface area semiconductors are rarely addressed and can result in erroneous values of two important parameters, i.e. flat band position and donor or acceptor densities. This work provides further insights into important electrochemical aspects and catalytic properties of high surface area nanomaterials for photoelectrochemical applications. Graphical abstract: fx1